EMPOWERMENT OF BEHAVIORAL COMPETENCY OF WOMEN IN KERALA- A KUDUMBASHREE MODEL (Sai Om Journal of Commerce & Management, 2015)
Empowerment of women and their participation in the development process has been considered as an essential feature of development of a nation. In India, women especially from the rural parts of the country suffer from being economically and socially suppressed by the male dominated society. Their thoughts and opinions are never considered by anyone in the society. Even they don’t have the right to take decision on maters related with their future. It is presumed that real nation development is possible only if the men and women work in equal terms. The Kudumbashree is a real example for the empowerment of women both in social as well as economic status. The Kudumbashree project first started in Kerala in the year 1998. The ultimate objective of the Kudumbashree scheme is to improve the standard of living of poor rural women by setting up micro-credit and productive enterprises. It is started as a joint programme of the Government of Kerala and NABARD implemented through Community Development Societies of Poor Women, serving as the community wing of Local Governments. The study mainly focuses on the empowerment of behavioral competency of rural women through Kudumbashree units. It shows that the majority of economically backward rural women people are working in Kudumbashree units and they got a notable level of improvement in various behavioral competencies. The Kudumbashree in Kerala is real model to follow for the rest of the states in India to empower the rural women.